2019
DOI: 10.7454/psr.v6i2.4172
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetics activity of salam koja (murraya koenigii ) leaves tea bag

Abstract: Background: Koja bay leaves (Murraya koenigii) which mostly cultivated in Indonesia and the leaves usually used by Aceh people as a flavoring agent for food, has been known to have an antidiabetic effect. In this study, we analyzed the antidiabetic effect of koja bay leaves tea bags which commercially available. Methods: The two variant doses of koja bay leaves tea bag (411.11 mg/g body weight and 822.22 mg/g body weight) were administered to 25 male rats which divided into five groups. The antidiabetic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Sudha et al 59 stated that its aqueous leaf extract was superior to glibenclamide in STZ-induced diabetic rats. Its leaves in tea bags have comparable activity with glibenclamide in reducing the blood glucose levels in alloxan-induced diabetes Wistar albino rats 71 . A single oral administration of variable dose levels of aqueous extract of M. koenigii showed a marked improvement in the sub, and mild diabetic rabbits in glucose tolerance test, and they suggested that it may be prescribed for controlling diabetes mellitus 6 .…”
Section: In Vivo Animal Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Sudha et al 59 stated that its aqueous leaf extract was superior to glibenclamide in STZ-induced diabetic rats. Its leaves in tea bags have comparable activity with glibenclamide in reducing the blood glucose levels in alloxan-induced diabetes Wistar albino rats 71 . A single oral administration of variable dose levels of aqueous extract of M. koenigii showed a marked improvement in the sub, and mild diabetic rabbits in glucose tolerance test, and they suggested that it may be prescribed for controlling diabetes mellitus 6 .…”
Section: In Vivo Animal Studiesmentioning
confidence: 90%
“…Hypoglycaemic effect in diabetic ob/ob mice 70 leaves tea bag Hypoglycaemic effect in alloxan-induced wistar albino rats 71…”
Section: Leaf Extractmentioning
confidence: 99%
“…Mahanimbine may lower blood sugar levels by potentiating the effects of insulin, either by boosting pancreatic insulin secretion from beta cells of the islets of Langerhans or by enhancing peripheral glucose uptake (47). When compared to acarbose, mahanimbine had a noticeable alpha amylase inhibitory effect (82). However, given that plant substances act more slowly than synthetic drugs and…”
Section: Murraya Koenigiimentioning
confidence: 99%
“…Nandy SK (2023) -10.58920/sciphy02020107 https://etflin.com/sciphy 117 that higher dosages may have a plateau effect, which would be harmful to the treatment of diabetes, longterm research is necessary (3, 81). It will need more research to extract and pinpoint the precise active ingredients that give the examined plant materials their antidiabetic properties (11,82).…”
Section: Sciences Of Phytochemistrymentioning
confidence: 99%
“…Curry leaves are frequently used to treat diabetes, and there are some studies showing that Mahanimbine has anti-diabetic properties. [16][17][18][19] Mahanimbine was determined using a variety of spectroscopic and chromatographic techniques. [20][21][22] For the purpose of determining the presence of Mahanimbine in various extracts of Murraya koenigii leaves extracted using traditional and non-conventional extraction techniques, a simple, accurate, and reproducible HPLC method has been developed and validated in the current work.…”
Section: Introductionmentioning
confidence: 99%